How do primary care physicians respond when patients cry during routine ambulatory visits?. (March 2014) - Stults, Cheryl D.; Elston Lafata, Jennifer; Diamond, Lisa; MacLean, Lisa; Stone, Ashley L.; Wunderlich, Tracy; Frankel, Richard M.; Tai-Seale, Ming
<x content-type="archive" xml:space="preserve">Abstract</x> Although crying is universally recognized as a sign of distress in adults, its role in assessing and diagnosing depression in medical settings has received little attention. We sought to describe the interactional circumstances surrounding patients who cry during routine periodic health examinations and the subsequent actions of their physicians. Qualitative content analysis of audio-recorded visits and administrative claims data for adult primary care patients for one year before and after an index visit were used to explore the context of patients' crying and how physicians responded. Most patients began to cry while discussing emotional pain over the loss or illness of a loved one. While physicians generally responded with immediate expressions of empathy, the intensity of their responses varied. Some patients received minimal assessment regarding their mental health, whereas others were assessed more extensively. Although most physicians did express empathy in response to patients' tears, some did not systematically assess patients' mental health status and overall functioning. Physicians may want to view crying as a sign of distress and more fully evaluate whether it fits into a more complex clinical presentation of depression.